The Urgency of Applying the Principles of Accuracy and Public Interest in the Evaluation Process and the Imposition of Administrative Sanctions on Mining Business Permits - Natasha, Evelyn; Sitabuana, Tundjung Herning (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
This article analyzes the urgency of applying the principles of due diligence and public interest in evaluating and imposing administrative sanctions on Mining Business Permits (IUP) in Indonesia. Using normative legal research methods, the study examines statutory regulations, principles of administrative law, and decisions of the Administrative Court (PTUN) to assess the consistency of government actions in mining oversight. The findings indicate that many IUP revocation decisions are overturned because of insufficient data verification, the absence of on-site inspections, and the failure to consider community and environmental impacts. This demonstrates that these two principles are essential prerequisites for ensuring the legality, accountability, and social legitimacy of administrative decision-making. The article recommends strengthening coordination between central and regional governments, enhancing supervisory capacity, and involving local communities as key strategies for improving mining governance and promoting more accountable administrative law enforcement.